The boy who cried wolf - Daubney, Kate; Aesop (Thaxted : Miles Kelly, 2016)
George, a shepherd boy repeatedly tricks villagers by falsely crying "Wolf!" for fun. When a real wolf appears, no one believes him, and the wolf attacks his flock.
Age 3+.
Keywords: Truthfulness and falsehood -- Juvenile fiction